Comparing the efficacy and safety of safinamide with rasagiline in China Parkinson’s disease patients with a matching adjusted indirect comparison - Yuyan Tan; Qianqian Wei; Pingyi Xu; Enxiang Tao; Lijiao Wang; Carlo Cattaneo; Huifang Shang; Shengdi Chen (Scientific Reports)
Abstract Safinamide and rasagiline are adjuncts to levodopa for the motor fluctuations of Parkinson’s Disease (PD). However, there remains a scarcity of head-to-head studies that directly compare safinamide and rasagiline. This study compared safinamide and rasagiline as adjuncts to levodopa in Chinese PD patients with motor fluctuations by matching-adjusted indirect comparison. Baseline age, sex, BMI, and OFF time were adjusted for matching. Efficacy outcomes were the mean changes in total daily OFF time, UPDRS III, and PDQ-39 from baseline to week 16, which calculated by a weighted covariance model. Safety outcomes included rates of AEs, SAEs, and DCAEs. Bucher method was used for mean difference (MD) of efficacy and odds ratio (OR) of safety outcomes. Combination therapy of safinamide 50-100 mg/day and levodopa significantly reduced the mean total daily OFF time by 0.7 h (− 1.40 to − 0.02) compared to the combination therapy of rasagiline 1 mg/day and levodopa. Safinamide more effectively reduced UPDRS III (− 2.9, − 5.28 to − 0.52). Changes in PDQ-39 scores indicated a trend toward greater improvement in safinamide. There was no significant difference in safety outcomes. Compared to rasagiline, the combined therapy of safinamide and levodopa could significantly improve motor fluctuations for PD patients in China, without compromising safety.